APPLICATION OF INNOVATIONS IN CULTURAL TOURISM - Konstantinova, Yoana (E-Journal VFU, 2024)
This article contributes to the academic debate on innovation in cultural tourism. The main goal of the research is to establish the potential for innovative development of cultural 763 tourism in tourist destinations. A model for evaluation and analysis of cultural tourism in tourist destinations has been proposed. An empirical approach was used to achieve the set goal. The results show that cultural tourism provides a wide range of opportunities for innovation which should contribute to its development. The proposed model can be successfully used for identifying problematic areas and implementing effective innovation solutions. For the purposes of the research, sources in several languages were used, including Bulgarian, English, Italian and Russian.